ANALISIS iREGRESI iLINIER iBERGANDA: iKETEPATAN iPENGIRIMAN iDAN iKEAMANAN iBARANG iSEBAGAI iPREDIKTOR iKEPUASAN iPELANGGAN iPADA iKONSUMEN iJ&T iKABUPATEN iJEPARA - prasetyo, iwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The ipurpose iof ithis istudy iwas ito ianalyze ithe iextent ito iwhich ithe ivariables iof idelivery iaccuracy i(X1) iand iproduct isecurity i(X2) iinfluence icustomer isatisfaction i(Y) iat iJ&T iExpress iin iJepara. iA iquantitative imethod iwas iapplied iwith imultiple iregression ianalysis ion i100 isamples irandomly iselected ithrough ia iquestionnaire. iData iprocessing iusing iSPSS iversion i26 isoftware irevealed ithat idelivery iaccuracy i(X₁) ihad ia ipositive iand isignificant ieffect ion icustomer isatisfaction i(β=0.968; ip=0.000), iwhile iproduct isecurity i(X₂) iwas iinsignificant i(β=-0.047; ip=0.603). iThe iAdjusted iR² ivalue iof i0.796 iindicates ithat i79.6% iof ithe ivariation iin icustomer isatisfaction i(Y) ican ibe iexplained iby ithese itwo ivariables: idelivery iaccuracy i(X1) iand iproduct isecurity i(X2). iThis istudy iconcludes ithe iimportance iof ioptimizing idelivery iaccuracy ias ia itop ipriority iwithout ineglecting iproduct isecurity ias ia icustomer ineed.